Victimology of The Palm Oil Land Dispute Case Between PT Permata Hijau Pasaman and The Community of Nagari Kapa, West Pasaman Regency - Sari, Armita; Nesti, Meksi Rahma; Wahyudi, M. (Bhandar: Harvesting Community Service in Asia, 2024)
The research examines the role of forensic victimology to provide legal protection for victims of the palm oil land conflict between PT. Permata Hijau Pasaman and the people of Kapa Village, West Pasaman Regency. Data for this study was obtained from social media observations. In addition to using forensic linguistics as the primary approach, the BREAK theory is applied to analyze the political, economic, policy, and social aspects of the conflict. The findings indicate that the discourse surrounding the conflict has escalated over time. The study highlights the failure of local policies, which have not been communicated effectively, as well as the uncooperative actions that have fueled the conflict since 1997. Furthermore, the legal protection provided in this case has been insufficient, leaving the victims vulnerable. This research underscores the need for better-informed local policies and more robust legal support for resolving conflicts such as this one.